Glucosamine Hydrochloride but Not Chondroitin Sulfate Prevents Cartilage Degradation and Inflammation Induced by Interleukin-1α in Bovine Cartilage Explants. (January 2016) - Bascoul-Colombo, Cécile; Garaiova, Iveta; Plummer, Sue F.; Harwood, John L.; Caterson, Bruce; Hughes, Clare E
Objective: Glucosamine hydrochloride (GH) and chondroitin sulfate (CS) are commonly used for the treatment of osteoarthritis (OA). The aim of this study was to assess their effects, alone and in combination, on preventing aggrecan degradation and inflammation in an in vitro model of OA. Design: To test the effects of GH and/or CS as a preventative treatment, cartilage explants were pretreated with the compound(s) using concentrations that showed no detrimental effect on chondrocyte viability. Interleukin-1α (IL-1α) was added to induce cartilage degradation, supernatant and explants were analyzed for proteoglycan degradation products, aggrecanase mRNA expression and activity, and for the release of inflammatory markers. Results: Following treatment with IL-1α, 2 mg/mL dose of GH pretreatment was associated with a reduction of glycosaminoglycan release, reduced generation of the pathological interglobular domain aggrecan catabolites, decreased mRNA levels of ADAMTS-4 and -5 and reduced activity of ADAMTS-4. In contrast, CS alone did not have a significant effect on IL-1α-induced cartilage degradation and the addition of 0.4 mg/mL CS to 2 mg/mL GH did not further inhibit IL-1α-induced activity. Pretreatment with 2 mg/mL GH also reduced the release of inflammatory markers, prostaglandin E2 and nitric oxide induced by IL-1α while CS did not have a significant effect. Conclusions: The results suggest that GH prevents cartilage degradation mediated by aggrecanases ADAMTS-4 and -5, and may also reduce inflammation. This could be part of the mechanisms by which GH is effective in maintaining joint integrity and function, and preventing or delaying early symptoms of OA.